The role of the primary balance in assessing the financial situation of local government - Wiśniewski, Marcin; Budzeń, Daniel (Research Papers in Economics and Finance, 2025)
The key aspect of assessing the financial condition of local government units in Poland is compliance with the individual debt repayment and service ratio. Equally important is the budget balance – especially if it is negative, in which case funding sources must be identified. The operating balance, the difference between current revenues and expenditures, also significantly impacts debt service ability and is embedded in the Polish legal-financial framework.Currently, financial assessments focus mainly on the budget and operating balances. However, the authors propose incorporating an additional measure – the primary balance – defined as the difference between total revenues and expenditures, excluding debt servicing. This study aims to apply the primary balance to evaluate the financial condition of all local government units in Poland over 2004–2023. The findings confirm the value of using the primary balance as a key indicator of financial stability.